2016
DOI: 10.1039/c5gc02264a
|View full text |Cite
|
Sign up to set email alerts
|

Maghemite decorated with ultra-small palladium nanoparticles (γ-Fe2O3–Pd): applications in the Heck–Mizoroki olefination, Suzuki reaction and allylic oxidation of alkenes

Abstract: γ-Fe2O3–Pd NPs for Heck, Suzuki and allylic oxidation reaction under milder conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(47 citation statements)
references
References 65 publications
(37 reference statements)
3
44
0
Order By: Relevance
“…A comparison of the PXRD patterns of TATAE and Pd/TATAE revealed that the structure of TATAE was well preserved after the treatment with Pd(OAc) 2 . In addition, the d ‐spacing and diffractions patterns of TATAE and Pd/TATAE showed a similar patterns, but the Pd/TATAE new peak was observed in these 2θ values 12.40°, 12.56°, 40.33° indicating that Pd(OAc) 2 coordinated with (C=N) imine bond and π‐π stacking of the conjugated aromatic ring, which is consistent with reported literature . Shuliang Xu et al .…”
Section: Resultssupporting
confidence: 89%
“…A comparison of the PXRD patterns of TATAE and Pd/TATAE revealed that the structure of TATAE was well preserved after the treatment with Pd(OAc) 2 . In addition, the d ‐spacing and diffractions patterns of TATAE and Pd/TATAE showed a similar patterns, but the Pd/TATAE new peak was observed in these 2θ values 12.40°, 12.56°, 40.33° indicating that Pd(OAc) 2 coordinated with (C=N) imine bond and π‐π stacking of the conjugated aromatic ring, which is consistent with reported literature . Shuliang Xu et al .…”
Section: Resultssupporting
confidence: 89%
“…The silanol groups on silica can be used for the covalent attachment of functional groups . Pd NPs and functional groups that bear magnetic particles, such as γ‐Fe 2 O 3 (maghemite) and Fe 3 O 4 (magnetite), are magnetically recoverable and have been envisaged for sustainable technology . An alkoxysilane coating on Fe 3 O 4 can impart chemical stability and provides precursor sites to anchor desirable nanocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Pd‐Promoted α ‐alkenylation of ketone 22 gave tetracyclic compound 23 , involving a ring closure step as well as an in situ allylic oxidation. The presence of adventitious molecular oxygen in the medium enabled Pd nanoparticles to catalyze the reaction …”
Section: Resultsmentioning
confidence: 99%